Mainstreaming Religious Moderation in Facing the Shift of Terrorism Movement Patterns in Indonesia - Khamdan, Muh; Umi Latifah; Mohd Syakir Mohd Rosdi; Naser Ali Abdulghani (International Journal of Religious and Interdisciplinary Studies, 2024)
This article discusses the role of religious moderation in dealing with the changing pattern of terrorism movements in Indonesia. Terrorism, which has been a serious threat since the 2002 Bali bombings, continues to evolve with increasingly complex movement patterns. The Government of Indonesia has taken steps to address it, including implementing the Terrorism Law, but challenges remain, especially regarding the often subjective definition of terrorism. This article aims to answer the question: How can religious moderation effectively deal with terrorism in Indonesia? This study uses qualitative methods and content analysis to analyze the synergy between the government and civil society, especially faith-based organizations such as Nahdlatul Ulama and Muhammadiyah, in building community resilience against extremist ideologies. The study's findings suggest that the religious moderation approach, which involves cooperation between religious leaders and the government, can reduce the escalation of terrorism through a soft-power approach. The main scholarly contribution of this article is the emphasis on the importance of a more effective and sustainable approach to religious moderation in handling terrorism, as well as the need for synergy between the government and civil society actors in preventing radicalization at the grassroots level.